Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Retensi Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada CV. Ari Putri - Raihana Adzqia (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of compensation and work environment on employee retention with job satisfaction as an intervening variable at CV. Ari Putri. This research employs a quantitative approach using purposive sampling. The population consists of all employees of CV. Ari Putri, with a total sample of 34 respondents. The data analysis technique used is Structural Equation Modeling Partial Least Square (SEM-PLS). The results indicate that: (1) compensation has a significant effect on job satisfaction; (2) work environment has a significant effect on job satisfaction; (3) compensation has a significant effect on employee retention; (4) work environment has a significant effect on employee retention; (5) job satisfaction has a significant effect on employee retention; (6) compensation significantly affects employee retention through job satisfaction; and (7) work environment significantly affects employee retention through job satisfaction. These findings suggest that improving compensation systems and work environment conditions can enhance job satisfaction, which ultimately strengthens employee retention.